2014
DOI: 10.1007/s00330-014-3412-6
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric assessment of tumour response using functional MR imaging in patients with hepatocellular carcinoma treated with a combination of doxorubicin-eluting beads and sorafenib

Abstract: Objective To prospectively assess treatment response using volumetric functional magnetic resonance imaging (MRI) metrics in patients with hepatocellular carcinoma (HCC) treated with the combination of doxorubicin-eluting bead–transarterial chemoembolization (DEB TACE) and sorafenib. Methods A single center study enrolled 41 patients treated with systemic sorafenib, 400 mg twice a day, combined with DEB TACE. All patients had a pre-treatment and 3–4 week post-treatment MRI. Anatomic response criteria (RECIST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…In our study, among patients who were assessable for radiologic response (n = 33) at 6-month follow-up, the overall disease control rate, which was based on both RECIST and EASL criteria, was 94%, a clearly encouraging result. In addition, median tumor enhancement changed from 80% at baseline to 15% at 6 months (20). These data strongly suggest that the combination of DEB TACE and sorafenib therapy was effective in decreasing intrahepatic tumor burden and, in turn, controlling disease progression in the liver.…”
Section: Discussionmentioning
confidence: 50%
“…In our study, among patients who were assessable for radiologic response (n = 33) at 6-month follow-up, the overall disease control rate, which was based on both RECIST and EASL criteria, was 94%, a clearly encouraging result. In addition, median tumor enhancement changed from 80% at baseline to 15% at 6 months (20). These data strongly suggest that the combination of DEB TACE and sorafenib therapy was effective in decreasing intrahepatic tumor burden and, in turn, controlling disease progression in the liver.…”
Section: Discussionmentioning
confidence: 50%
“…In some studies investigators have estimated the percent change in tumour enhancement visually, as is often done in clinical practice [14, 15]; however, in other studies, the enhancing tissue has been measured uni- [16] or bidimensionally [11, 17] or by using a volumetric approach [1821]. Furthermore, in all of these studies, the magnitude of response was decided in consensus without analyzing interreader agreement.…”
Section: Introductionmentioning
confidence: 99%
“…Tumor necrosis after TARE occurs centrally, and therefore, 3D assessment is more representative of the changes that occur globally within a targeted lesion. Furthermore, the software enabled easy and better reproducibility analysis of multiparametric MR imaging data compared to ROI-based axial measurements [15,24,28]. The presented data by Chapiro et al [29] provided multilayer proof of the precision of 3D quantitative perfusion and diffusion-weighted MR imaging when correlated with pathologic examination as a standard of Ref.…”
Section: Discussionmentioning
confidence: 73%
“…While tumor shrinkage may not be initially apparent, there were changes in tumor ADC and enhancement that could be valuable in assessing early therapeutic efficacy [21][22][23]. Previous studies [4,15,24] demonstrated the promising role of quantitative volumetric functional MRI to detect early tumor response to LRT of liver malignancies. Changes in volumetric functional MR metrics may precede conventional tumor size changes, potentially overcoming the limitations of mRECIST and EASL.…”
Section: Discussionmentioning
confidence: 95%